MANAGEMENT OF ANTIPHOSPHOLIPID SYNDROME IN ADULTS: THE EUROPEAN LEAGUE AGAINST RHEUMATISM (EULAR) RECOMMENDATIONS - Veselinović, Mirjana (Medicinski časopis, 2020)
Antiphospholipid syndrome (APS) is a rare disease characterised by venous and/or arterial thrombosis, pregnancy complications and the presence of specific autoantibodies called antiphospholipid (aPL)antibodies.The European League Against Rheumatism, EULAR, has published a set of recommendations for the management of antiphospholipid syndrome in adults,based on the systematic literature reviews (SLRs) results and expert opinion. Lowdose aspirin (LDA) is recommended for asymptomatic aPL carriers, patients with systemic lupus erythematosus without prior thrombotic or obstetric APS, and nonpregnant women with a history of obstetric APS only, all with high-risk aPL profiles. Patients with APS and first unprovoked venous thrombosis should receive long-term treatment with vitamin K antagonists (VKA) with a target international normalised ratio (INR) of 2–3. In patients with APS with first arterial thrombosis, treatment with VKA with INR 2–3 or INR 3–4 is recommended, considering the individual’s bleeding/ thrombosis risk. For patients with recurrent arterial or venous thrombosis despite adequate treatment, addition of LDA, increase of INR target to 3–4 or switch to low molecular weight heparin may be considered. In women with prior obstetric APS, combination treatment with LDA and prophylactic dosage heparin during pregnancy is recommended. In patients with recurrent pregnancy complications, increase of heparin to therapeutic dose, addition of hydroxychloroquine or addition of low-dose prednisolone in the first trimester may be considered. These recommendations aim to guide treatment in adults with APS.